Importance of the role of mothers in stunting prevention efforts - Irnawati Irnawati; Uliarta Marbun; Hasnita (LPPM Politeknik Sandi Karsa, 2025)
Stunting is a growth and developmental disorder in children caused primarily by chronic malnutrition and inadequate access to essential nutrients during critical early childhood. Mothers with adequate nutritional knowledge tend to prioritise their children’s dietary needs, enabling optimal growth and development. Preventing stunting is vital due to its long-term impacts on physical, cognitive, and economic potential. This community service activity aimed to enhance mothers' and families' knowledge, awareness, and skills in stunting prevention from an early stage. The program involved 20 women of reproductive age in the working area of Pattingalloang Health Center, Makassar. Activities included health education through socialization, discussions, and distribution of leaflets covering definitions, causes, prevention, and management of stunting. Interactive counseling sessions emphasized the importance of the First 1,000 Days of Life, balanced nutrition, exclusive breastfeeding, and appropriate complementary feeding practices. The high participation and engagement rates reflected increased enthusiasm and awareness regarding stunting, an issue often underestimated in the community. Key supporting factors included active participation, health worker collaboration, and adequate facilities, while limiting factors involved time constraints and fewer participants than targeted. The program significantly improved mothers’ understanding of their crucial role in stunting prevention and demonstrated that community-based, participatory interventions effectively support national stunting reduction goals